Protein Detection - Tutar, Yusuf; Tutar, Lütfi (Biochemistry, 2022)
The book explores distinct aspects of protein purification and characterization steps. It discusses solubility problems, resin selection tricks, and essential credentials in a purification process. In addition, the book examines aggregation and proteinopathy-related protein detection methods and reviews several essential protein detection and characterization methods in cancer for diagnosis, prognosis, and therapy, such as enzyme-linked immunosorbent assay (ELISA), immunohistochemistry, flow cytometry, western blot, mass spectrometry, and others.